Dydaktyka literatury: "świadomość brezpośrednia" i "wiedza krytyczna" = Literature didactics: the "direct consciousness" and the "critical knowledge" - Pasterniak, Wojciech (1935-2018); Pasterniak, Lilla (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The paper discusses the two basic phases of the development of literatura didactics: the theoretical stage and the pre-theoretical stage.
Keywords: dydaktyka literatury